Aernout van Buchel’s Iter Italicum on-line - de Jong, Jan (Incontri. Rivista europea di studi italiani, 2021)
Review of: Arnoldus Buchellius (Aernout van Buchel), Diarium (Commentarius rerum quotidianarum, including Iter Italicum). Transcription with preface and annotations of Hs. 798 (parts I and II), in the University Library of Utrecht.